Laboriosos e morigerados ou indolentes e vadios: as múltiplas imagens do imigrante e do trabalhador livre nacional nos relatórios governamentais entre 1847 e 1882 no Espírito Santo - Soprani, Joel (2015)
From 1847 to 1882, the province of Espirito Santo went through the process of formation of immigrant colonies (state or private). Primarily European, the colonies were within a broad imperialist government program to import labor into the territorial colonization of the country and to substitute slave labor. Within this context were formed the colonies of Santa Isabel, Rio Novo, and Santa Leopoldina. These three colonies were those with the most regional development. This trajectory is reported in the following official documents: the province’s empire minister’s, president’s and vice president’s reports of the province who, over the years, presented bureaucratic information but also expressed opinions, often pejorative ones, toward immigrants. Such opinions would vary between the period’s respective ruler and it is around these opinions that this thesis will be focused on. This thesis is centered around these opinions, and it was formulated within the Estado e Políticas Públicas do Programa de PósGraduação de História da Universidade Federal do Espírito Santo (PPGHIS-Ufes) guidelines.